Resuscitation of Preterm Newborn with High Concentration Oxygen Versus Low Concentration Oxygen - Zohreh Badiee; Amir Mohammad Armanian (مجله دانشکده پزشکی اصفهان, 2011)
Background: It is well known that a brief exposure to 100% oxygen for only a few minutes could be toxic to the preterm infant. We compared the effectiveness of neonatal resuscitation with low concentration oxygen (30%) and high concentration oxygen (100%). Methods: Thirty two preterm neonates with gestational age 29-34 weeks who required resuscitation were randomized into two groups. In low concentration oxygen group (LOG), resuscitation begun with 30% O2. Infants were examined every 60 to 90 seconds, and if their heart rate was less than 100, 10% was added to the previous FIO2 until the heart rate increased to 100 and SO2 increased to 85 percent. In high concentration oxygen group (HOG) resuscitation begun with 100% O2 and every 60 to 90 seconds, FIO2 was decreased 10–15% until the heart rate reached to 100 and SO2 reached to 85 percent. Findings: The FIO2 in LOG was increased stepwise to 45% and in HOG was reduced to 42.1% to reach stable oxygen saturation more than 85% at 5th minute in both groups. At first and third minutes after birth and there was no significant differences between groups in heart rate, and after 1, 2, 4 and 5 minutes after birth there was no significant differences in oxygen saturation (SO2) between groups, regardless of the initial FIO2. Conclusion: We can safely initiate resuscitation of preterm infants with a low FIO2 (approximately 30%) oxygen and then oxygen should be adjusted with the neonates needs.